2002
DOI: 10.1248/cpb.50.1223
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-Substituted Piperazinyl Carbamoyl and Acetyl Derivatives of Tetrahydropapaverine: Potent Antispasmodic Agents.

Abstract: The synthesis and structure-activity-relationship (SAR) for a series of N-substituted piperazinyl carbamoyl 7-15 and piperazinyl acetyl 18-26 derivatives of tetrahydropapaverine have been carried out. The general synthetic methods of carbamoyl tetrahydropapaverine analogues involve N-substituted piperazines and carbamoyl imidazole tetrahydropapaverine as starting materials. Another route for synthesizing these compounds, involving the formation of carbamoyl imidazole piperazine has also been explored. Acylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…Compound 22 was found to be the most potent compound among the series. However, contrary to our predictions, none of the bis analogues were able to beat the best compound of our previously reported 26) piperazinyl based tetra substituted urea derivative of papaverine.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Compound 22 was found to be the most potent compound among the series. However, contrary to our predictions, none of the bis analogues were able to beat the best compound of our previously reported 26) piperazinyl based tetra substituted urea derivative of papaverine.…”
Section: Resultscontrasting
confidence: 99%
“…Tetrahydropapaverine efficiently displaced one of the imidazole rings of carbonyldiimidazole 26) to give tetrahydropapaverine carbamoyl imidazole 19 on refluxing it with carbonyldiimidazole (CDI) in tetrahyrofuran (THF) for 24 h. The reaction of methyl iodide with carbamoyl imidazole 19 (4 molar equivalents) in acetonitrile for one day at room temperature produced the imidazolium salt quantitatively. This imidazolium salt required no additional purification for final conversion to ureas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier communication from our laboratory (11,12), we documented the vasodilative effects of papaverine analogsand reported that analogsof this opium alkaloid possesses potent antispasmodic activity. The present study was a step ahead to evaluate the effect of oral administration of papaverine (an opium alkaloid known for its vasodilative effect (13,14), on the GST activity and GSH content in the rat liver and lung for its presumptive role in chemoprevention of chemical carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…noscapine (15,16) and papaverine (17).Cryptopine, (Figure 1) a non narcotic alkaloid remains in the tarry waste mother liquors that are left behind after the removal of morphine and codeine from opium. In 1918, Watt (18) commented on the relatively high content of cyptopine in Indian opium (about 0.3 %) which is high for this alkaloid, only seventh in average amount in opium.…”
Section: Introductionmentioning
confidence: 99%